PARADIGMA DAKWAH TRANSFORMATIF PADA LEMBAGA PENDIDIKAN PESANTREN (Kajian Peran dan Tanggung Jawab Pesantren di Era Modern) - Kholid Suhaemi (Al Qalam, 2016)
This paper aims to explore the paradigm of transformative dakwah (religious dissemination) in pesantren (Islamic boarding schools). In general, dakwah is some sort of responsibility and real implementations of Islam, whereas the outcomes are men’s masterwork, individually or collectively (in organizations), presented to Allah. Dakwah is an Islamic obligation for its adherents. Dakwah is an actual effort in order to enforce justice, improve welfare, fertilize the equality, and achieve happiness on the basis of Allah’s sincerity. Therefore, dakwah will, teologically and sociologically, exist because Islam will remain until humans are gone, or Islam will still be a blessed religion, or a haq religion. In this paper, transformative dakwah is a dakwah model which not only relies on verbalistic calls (convensional) in disseminating religious materials or not only makes dai (preachers) conveyors of religious messages, but also internalizes the messages in people’s real life by directly accompanying people. These tasks can be conducted by dai individually or collectively in the community in the forms of social organizations or educational institutions, such as pesantren. Keywords: Transformative dakwah, pesantren, dai, kiai, dakwah paradigm